Efficiency enhancement of MAPbIxCl3−x based perovskite solar cell by modifying the TiO2 interface with Silver Nanowires. (June 2016) - Huang, Jin; Wang, Minqiang; Ding, Lei; Igbari, Femi; Yao, Xi
Highlights: A novel electrode was fabricated with embedded Silver Nanowires. The embedded effect of Silver Nanowires was investigated by SEM and I–V. Electrode with embedded, on top and pristine TiO2 were successfully fabricated. Significant reduction in hysteresis for MAPbI x Cl3 − x based Perovskite Solar Cell. Abstract: A network of Silver Nanowires (AgNWs) sandwiched between titanium oxide (TiO2 ) films fabricated by solution-process was applied as electron conductor in MAPbI x Cl3− x -based perovskite solar cell. This network can prevent the formation of space limited charge existing between perovskite and AgNWs. As a result, a high performance of 12.55% was achieved, with a short circuit current density of 19.35 mA/cm 2, an open circuit voltage of 0.94 V and a fill factor of 0.69. We investigated the charge separation and transport properties. Compared to the other two situations (the pristine TiO2 compact films and TiO2 with AgNWs as a top layer), the incorporation of TiO2 /AgNWs/TiO2 films led to lower leakage current density, smaller series resistance, more smooth surface coverage and larger recombination resistance. This explains the improved Jsc and FF obtained for the perovskite solar cell with TiO2 –AgNWs (embedded).